Down to Earth: Geographic Information for Sustainable Development in Africa - National Research Council
In 1992, world leaders adopted Agenda 21, the work program of the 1992 U.N. Conference on Environment and Development. This landmark event provided a political foundation and action items to facilitate the global transition toward sustainable development. The international community marked the tenth anniversary of this conference in Johannesburg, South Africa, in August 2002. Down to Earth, a component of the U.S. State Department's \

Community and Quality of Life: Data Needs for Informed Decision Making - National Research Council
\

Research Opportunities in Geography at the U.S. Geological Survey - National Research Council (The National Academies Press, 2002)
Research Opportunities in Geography at the U.S. Geological Survey (USGS) provides perspective and guidance to the geography discipline about its future research and strategic directions. The report makes specific recommendations about scientific research priorities and partnerships within and outside the agency, and outlines a long-term core research agenda for the USGS.

Emerging Issues in Hispanic Health: Summary of a Workshop - National Research Council (The National Academies Press, 2002)
Hispanics are defined as people of Spanish-speaking origin from Latin America, the Caribbean, or Europe. Hispanics vary in terms of socioeconomic status, race, religion and\/or more. A common occurrence among the Hispanics, however, are the emerging issues concerning their health.It is estimated that by 2050 Hispanics will make up more than 25% of the United States' population. It is thus important that they have the resources to contribute maximally to American society. This can come about by first understanding and dealing with issues surrounding their health. In hopes of examining these issues and as a part of its continuing commitment to promote a national dialogue on race and diversity in the United States, the National Academies organized an expert meeting on Emerging Issues in Hispanic Health on April 10, 2002. Emerging Issues in Hispanic Health: Summary of a Workshop includes a review of key demographic data, such as population statistics, that characterize the Hispanic population in the United States; research on the socioeconomic, sociocultural, and behavioral determinants of health; effects of selective migration; the apparent epidemiological paradox : the relatively positive health outcomes observed in some Hispanic populations despite their relatively poor socioeconomic status or other types of disadvantage such as discrimination; and more.

Toward New Partnerships In Remote Sensing: Government, the Private Sector, and Earth Science Research - National Research Council (The National Academies Press, 2002)
The technical, scientific, policy, and institutional environment for conducting Earth science research has been changing rapidly over the past few decades. Changes in the technical environment are due both to the advent of new types and sources of remote sensing data, which have higher spatial and spectral resolution, and to the development of vastly expanded capabilities in data access, visualization, spatial data integration, and data management. The scientific environment is changing because of the strong emphasis on global change research, both nationally and internationally, and the evolving data requirements for that research. And the policy and institutional environment for the production of Earth observation data is changing with the diversification of both remote sensing data and the institutions that produce the data. In this report, the Space Studies Board's Steering Committee on Space Applications and Commercialization explores the implications of this changing environment, examining the opportunities and challenges it presents.

Enhancing Undergraduate Learning with Information Technology: A Workshop Summary - National Research Council (The National Academies Press, 2002)
Enhancing Undergraduate Learning with Information Technology reports on a meeting of scientists, policy makers, and researchers convened to discuss new approaches to undergraduate science, mathematics, and technology education. The goal of the workshop was to inform workshop participants and the public about issues surrounding the use of information technology in education. To reach this goal, the workshop participants paid particular attention to the following issues: What educational technologies currently exist and how they are being used to transform undergraduate science, engineering, mathematics, and technology education; What is known about the potential future impact of information technology on teaching and learning at the undergraduate level; How to evaluate the impact of information technology on teaching and learning; and What the future might hold.

A Review of the Florida Keys Carrying Capacity Study - National Research Council
Nearly thirty years ago the Florida Keys were designated as an Area of Critical State Concern. The state recognized that Monroe County contained many valuable natural, environmental, historical, and economic resources that required thoughtful management. In 1996, as a result of many years of discussion, negotiation, and litigation, the Florida Administration Commission issued an Executive Order requiring the preparation of a \

Estimating Water Use in the United States: A New Paradigm for the National Water-Use Information Program - National Research Council (The National Academies Press, 2002)
Across the United States, the practices for collecting water use data vary significantly from state to state and vary also from one water use category to another, in response to the laws regulating water use and interest in water use data as an input for water management. However, many rich bodies of water use data exist at the state level, and an outstanding opportunity exists for assembling and statistically analyzing these data at the national level. This would lead to better techniques for water use estimation and to a greater capacity to link water use with its impact on water resources.This report is a product of the Committee on Water Resources Research, which provides consensus advice to the Water Resources Division (WRD) of the USGS on scientific, research, and programmatic issues. The committee works under the auspices of the Water Science and Technology Board of the National Research Council (NRC). The committee considers a variety of topics that are important scientifically and programmatically to the USGS and the nation and issues reports when appropriate. This report concerns the National Water-Use Information Program (NWUIP).

Leveraging Longitudinal Data in Developing Countries: Report of a Workshop - National Research Council (The National Academies Press, 2002)
Longitudinal data collection and analysis are critical to social, demographic, and health research, policy, and practice. They are regularly used to address questions of demographic and health trends, policy and program evaluation, and causality. Panel studies, cohort studies, and longitudinal community studies have proved particularly important in developing countries that lack vital registration systems and comprehensive sources of information on the demographic and health situation of their populations. Research using data from such studies has led to scientific advances and improvements in the well-being of individuals in developing countries. Yet questions remain about the usefulness of these studies relative to their expense (and relative to cross-sectional surveys) and about the appropriate choice of alternative longitudinal strategies in different contexts.For these reasons, the Committee on Population convened a workshop to examine the comparative strengths and weaknesses of various longitudinal approaches in addressing demographic and health questions in developing countries and to consider ways to strengthen longitudinal data collection and analysis. This report summarizes the discussion and opinions voiced at that workshop.

Countering Terrorism: Lessons Learned from Natural and Technological Disasters (The National Academies Press, 2002)
Countering Terrorism is the summary of The Natural Disasters Roundtable Forum on Countering Terrorism, held at The National Academies in Washington, D. C. on February 28 00e220ac201c March 1, 2002.This event promoted a two-way process of knowledge exchange. In one direction, representatives of the hazard research community discussed lessons from past disasters that may help inform efforts to respond to and recover from acts of terrorism. In the other direction, key personnel who responded to the September 11 events, and to the anthrax bioterrorism that followed, helped to define new research needs applicable to terrorism.

Demographic Assessment Techniques in Complex Humanitarian Emergencies: Summary of a Workshop - National Research Council (The National Academies Press, 2002)
The Roundtable on the Demography of Forced Migration was established by the Committee on Population of the National Research Council in 1999. The roundtable is composed of experts from academia, government, philanthropy, and international organizations. The roundtable's purpose is to serve as an interdisciplinary, nonpartisan focal point for taking stock of what is known about demographic patterns in refugee situations, to apply this knowledge base to assist both policy makers and relief workers, and to stimulate new directions for innovation and scientific inquiry in this growing field of study. The roundtable meets yearly and has also organized a series of workshops (held concurrently with roundtable meetings) on some of the specific aspects of the demography of refugee and refugee-like situations, including mortality patterns, demographic assessment techniques, and research ethics in complex humanitarian emergencies. This report to the Roundtable on the Demography of Forced Migration is a summary of one such workshop, which was held on September 20-21, 2000, under the aupices of the Committee on Population. The purpose of this meeting was to address a basic problem faced by all humanitarian relief agencies in an emergency: how to count the numbers of displaced persons and assess their general well-being. Workshop participants examined different methods for estimating refugee populations and their mortality rates, whether mortality was due to disease and malnutrition or human rights abuses. Demographic Assessment Techniques in Complex Humanitarian Emergencies: Summary of a Workshop explores the applicability of various methods in different types of emergency settings, how to improve existing methodologies and develop new ones, and the difficulties encountered by personnel in the field, including security, logistics, and access to a population.

Effects of Trawling and Dredging on Seafloor Habitat - National Research Council (The National Academies Press, 2002)
Concerns over the potential ecological effects of fishing have increased with the expansion of fisheries throughout the marine waters of the United States. Effects of Trawling and Dredging on Seafloor Habitat describes how assessment of fishing impacts depends on gear type, number and location of bottom tows, and the physical and biological characteristics of seafloor habitats. Many experimental studies have documented acute, gear–specific effects of trawling and dredging on various types of habitat. These studies indicate that low mobility, long–lived species are more vulnerable to towed fishing gear than short–lived species in areas where the seabed is often disturbed by natural phenomena. Trawling and dredging may also change the composition and productivity of fish communities dependent on seafloor habitats for food and refuge. The scale of these impacts depends on the level of fishing effort. This volume presents color maps of fishing effort for all regions with significant bottom trawl or dredge fisheries – the first time that such data has been assembled and analyzed for the entire nation.

Natural Disasters and Energy Policy: A Summary of the Forum on Natural Diasters and Energy Policy, June 12, 2001, Washington, DC - National Research Council (The National Academies Press, 2002)

Report of a Workshop on Predictability and Limits-To-Prediction in Hydrologic Systems - National Research Council (The National Academies Press, 2002)
The Committee on Hydrologic Science (COHS) of the National Research Council (NRC) is engaged in studying the priorities and future strategies for hydrologic science. In order to involve a broad community representation, COHS is organizing workshops on priority topics in hydrologic science. These efforts will culminate in reports from the NRC on the individual workshops as well as a synthesis report on strategic directions in hydrologic science. The first workshop-Predictability and Limits-to-Prediction in Hydrologic Systems-was held at the National Center for Atmospheric Research in Boulder, Colorado, September 21-22, 2000. Fourteen technical presentations covered basic research and understanding, model formulations and behavior, observing strategies, and transition to operational predictions.

Guidance for the National Healthcare Disparities Report - Institute of Medicine (The National Academies Press, 2002)
The Agency for Healthcare Research Quality commissioned the Institute of Medicine establish a committee to provide guidance on the National Healthcare Disparities Report is of access to health care, utilization of services, and the services received. The committee was asked to con population characteristics as race and ethnicity, society status, and geographic location. It was also asked to examine factors that included possible data sources and types of measures for the report.

Review of NASA's Earth Science Enterprise Applications Program Plan (The National Academies Press, 2002)

Sea Level Rise and Coastal Disasters: Summary of a Forum, October 25, 2001, Washington DC (The National Academies Press, 2002)

National Capacity in Forestry Research - National Research Council (The National Academies Press, 2002)
Forests are major components of the earth's natural resources and they are increasingly critical to the welfare of the U.S. economy, environment, and population. Desires to improve forest management and productivity, preserve biodiversity, maintain ecologic integrity, and provide societal services, such as recreation and tourism, necessitate a strong forestry-research base.Given the clear importance of forestry research in sustaining forests for the future, the U.S. Department of Agriculture (USDA) Forest Service asked the Board on Agriculture and Natural Resources of the National Academies to undertake a study of the nation's capacity in forestry research. The Committee on National Capacity in Forestry Research was appointed to carry out the study, which was conducted to review the current expertise and status of forestry research and to examine the approaches of natural resources education and forestry-research organizations to meet future needs.

Opportunities to Improve the U.S. Geological Survey National Water Quality Assessment Program - National Research Council (The National Academies Press, 2002)
The U.S. Geological Survey (USGS) established the National Water Quality Assesment (NAWQA) program in 1985 to assess water quality conditions and trends in representative river basins and aquifers across the United States. With this report, the NRC's Water Science and Technology Board has provided advice to USGS regarding NAWQA five separate times as the program evolved from an unfunded concept to a mature and nationally–recognized program in 2002. This report assesses the program's development and representative accomplishments to date and makes recommendations on opportunities to improve NAWQA as it begins its second decade of nationwide monitoring.

Surface Transportation Environmental Research: A Long-Term Strategy – Special Report 268 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 268 - Surface Transportation Environmental Research: A Long-Term Strategy defines a broad and ambitious research program to address and inform major public policy debates about the effects of surface transportation facilities and operations on the human and natural environments. The committee that conducted the study identified major gaps in knowledge that could be filled through a cooperative program of research involving federal agencies, states, and environmental organizations. The committee recommended creation of a new cooperative research program to carry out its recommended research agenda. Special Report 268 Summary

Science and Its Role in the National Marine Fisheries Service - National Research Council (The National Academies Press, 2002)
NMFS has a difficult and complex task in managing U.S. marine fisheries. Despite some successes, too many stocks continue to decline. Over the past decade, several problems have been identified that have contributed to the current dissatisfaction with how marine fisheries are managed. This dissatisfaction is evident from the large number of lawsuits filed by the fishing industry and environmental organizations. One central problem is overfishing. Overfishing issues have been discussed in a series of NRC reports, and these reports identify overcapitalization, and technological and gear improvements as some of the causes. The reports recommend ways to stem these problems and to advance the practice of fishery science at NMFS. This report reiterates some of these recommendations, and makes new recommendations to enhance the use of data and science for fisheries management.

Riparian Areas: Functions and Strategies for Management - National Research Council (The National Academies Press, 2002)
The Clean Water Act (CWA) requires that wetlands be protected from degradation because of their important ecological functions including maintenance of high water quality and provision of fish and wildlife habitat. However, this protection generally does not encompass riparian areas2014the lands bordering rivers and lakes2014even though they often provide the same functions as wetlands. Growing recognition of the similarities in wetland and riparian area functioning and the differences in their legal protection led the NRC in 1999 to undertake a study of riparian areas, which has culminated in Riparian Areas: Functioning and Strategies for Management. The report is intended to heighten awareness of riparian areas commensurate with their ecological and societal values. The primary conclusion is that, because riparian areas perform a disproportionate number of biological and physical functions on a unit area basis, restoration of riparian functions along America2019s waterbodies should be a national goal.

Technology Development for Army Unmanned Ground Vehicles - National Research Council (The National Academies Press, 2002)
Unmanned ground vehicles (UGV) are expected to play a key role in the Army2019s Objective Force structure. These UGVs would be used for weapons platforms, logistics carriers, and reconnaissance, surveillance, and target acquisition among other things. To examine aspects of the Army2019s UGV program, assess technology readiness, and identify key issues in implementing UGV systems, among other questions, the Deputy Assistant Secretary of the Army for Research and Technology asked the National Research Council (NRC) to conduct a study of UGV technologies. This report discusses UGV operational requirements, current development efforts, and technology integration and roadmaps to the future. Key recommendations are presented addressing technical content, time lines, and milestones for the UGV efforts.

The Scientific Basis for Estimating Air Emissions from Animal Feeding Operations: Interim Report - National Research Council (The National Academies Press, 2002)
This is an interim report of the ad hoc Committee on Air Emissions from Animal Feeding Operations of the National Research Council's Committee on Animal Nutrition. A final report is expected to be issued by the end of 2002. The interim report is intended to provide the committee's findings to date on assessment of the scientific issues involved in estimating air emissions from individual animal feeding operations (swine, beef, dairy, and poultry) as related to current animal production systems and practices in the United States. The committee's final report will include an additional assessment within eight broad categories: industry size and structure, emission measurement methodology, mitigation technology and best management plans, short- and long-term research priorities, alternative approaches for estimating emissions, human health and environmental impacts, economic analyses, and other potential air emissions of concern.This interim report focuses on identifying the scientific criteria needed to ensure that estimates of air emission rates are accurate, the basis for these criteria in the scientific literature, and uncertainties associated with them. It also includes an assessment of the emission-estimating approaches in a recent U.S. Environmental Protection Agency (EPA) report Air Emissions from Animal Feeding Operations. Finally, it identifies economic criteria needed to assess emission mitigation techniques and best management practices.

Review of the NARSTO Draft Report: NARSTO Assessment of the Atmospheric Science on Particulate Matter - National Research Council (The National Academies Press, 2002)

Incorporating ITS Into the Transportation Planning Process: An Integrated Planning Framework (ITS, M&O, Infrastructure) Practitioner's Guidebook - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2002)
TRB2019s National Cooperative Highway Research Program (NCHRP) Web-Only Document 118, Part II: Incorporating ITS Into the Transportation Planning Process: An Integrated Planning Framework (ITS, M&O, Infrastructure) Practitioner2019s Guidebook explores factors that are pushing regions and states towards integration of intelligent transportation systems in the transportation planning process, including the institutional, organizational, and technical processes that are included within it. In addition, this report examines challenges, transition strategies, and resources available to help agencies interested in adopting the integrated framework concept. A companion overview of this report has been published as NCHRP Web-Only Document 118 Part I.

Community Programs to Promote Youth Development - National Research Council; Institute of Medicine (The National Academies Press, 2002)
After-school programs, scout groups, community service activities, religious youth groups, and other community-based activities have long been thought to play a key role in the lives of adolescents. But what do we know about the role of such programs for today's adolescents? How can we ensure that programs are designed to successfully meet young people's developmental needs and help them become healthy, happy, and productive adults? Community Programs to Promote Youth Development explores these questions, focusing on essential elements of adolescent well-being and healthy development. It offers recommendations for policy, practice, and research to ensure that programs are well designed to meet young people's developmental needs. The book also discusses the features of programs that can contribute to a successful transition from adolescence to adulthood. It examines what we know about the current landscape of youth development programs for America's youth, as well as how these programs are meeting their diverse needs. Recognizing the importance of adolescence as a period of transition to adulthood, Community Programs to Promote Youth Development offers authoritative guidance to policy makers, practitioners, researchers, and other key stakeholders on the role of youth development programs to promote the healthy development and well-being of the nation's youth.

Making the Nation Safer: The Role of Science and Technology in Countering Terrorism - National Research Council
Vulnerabilities abound in U.S. society. The openness and efficiency of our key infrastructures 2014 transportation, information and telecommunications systems, health systems, the electric power grid, emergency response units, food and water supplies, and others 2014 make them susceptible to terrorist attacks. Making the Nation Safer discusses technical approaches to mitigating these vulnerabilities. A broad range of topics are covered in this book, including: Nuclear and radiological threats, such as improvised nuclear devices and \

Publicly Funded Agricultural Research and the Changing Structure of U.S. Agriculture - National Research Council (The National Academies Press, 2002)
The U.S. Department of Agriculture (USDA) requested that the Board on Agriculture and Natural Resources of the National Research Council (NRC) convene a panel of experts to examine whether publicly funded agricultural research has influenced the structure of U.S. agriculture and, if so, how. The Committee to Review the Role of Publicly Funded Agricultural Research on the Structure of U.S. Agriculture was asked to assess the role of public-sector agricultural research on changes in the size and numbers of farms, with particular emphasis on the evolution of very-large-scale operations.

Geoscience Data and Collections: National Resources in Peril - National Research Council (The National Academies Press, 2002)
Geoscience data and collections (such as, rock and sediment cores, geophysical data, engineering records, and fossils) are necessary for industries to discover and develop domestic natural resources to fulfill the nation2019s energy and mineral requirements and to improve the prediction of immediate and long term hazards, such as land slides, volcanic eruptions and global climate change. While the nation has assembled a wealth of geoscience data and collections, their utility remains incompletely tapped. Many could act as invaluable resources in the future but immediate action is needed if they are to remain available. Housing of and access to geoscience data and collections have become critical issues for industry, federal and state agencies, museums, and universities. Many resources are in imminent danger of being lost through mismanagement, neglect, or disposal. A striking 46 percent of the state geological surveys polled by the committee reported that there is no space available or they have refused to accept new material. In order to address these challenges, Geoscience Data and Collections offers a comprehensive strategy for managing geoscience data and collections in the United States.

Estimating the Public Health Benefits of Proposed Air Pollution Regulations - National Research Council (The National Academies Press, 2002)
EPA estimates that thousands of premature deaths and cases of illnesses may be avoided by reducing air pollution. At the request of Congress, this report reviews the scientific basis of EPA's methods used in estimating the public health benefits from its air pollution regulations.

New Tools for Environmental Protection: Education, Information, and Voluntary Measures - National Research Council
Many people believe that environmental regulation has passed a point of diminishing returns: the quick fixes have been achieved and the main sources of pollution are shifting from large \

In War and Peace: My Life in Science and Technology - Guy Stever (The National Academies Press, 2002)
Science came into Guy Stever2019s life as a pure and peaceful pursuit. It was only later, as he walked through the wreckage of wartime London that he began to see science as central to a desperate struggle to survive. Past president of Carnegie Mellon University, former Chief Scientist of the U.S. Air Force, one-time Director of the National Science Foundation, professor at MIT for 20 years, member of the National Academies of Sciences and Engineering, and science advisor to two presidents2026Guy Stever was a central figure in twentieth century science2014consistently on the front lines, changing the fate of a nation. In this thoughtful and candid memoir, Stever recounts an extraordinary life that reveals as much about the man as about the major scientific and technological events of his day. Born of humble origins and orphaned at an early age, Stever journeyed from a small town in New York to work alongside British comrades who were developing and refining the critical radar technology that was to turn the tide of the war against the Germans. As a technical intelligence officer, these harrowing wartime years took him from the beachheads of Normandy to the German slave-labor factories responsible for building the V-2 rockets. Stever returned home committed to serving his country. He became intimately involved in America2019s nascent guided missile program2014and was to remain a key player in the anti-ballistic missile defense program that heralded the era of the Cold War. As the decades passed, Stever continued to exert lasting influence on countless scientific endeavors. He was instrumental in the formation of new institutions, from the creation of NASA in the post-Sputnik years to the merging of Carnegie Tech and the Mellon Institution, giving birth to Carnegie Mellon University. As Presidential Science Advisor to both Nixon and Ford, Stever shaped the very structure of contemporary presidential science advising. And he was to chair the oversight committee that redesigned the space shuttle boosters after the Challenger explosion. Guy Stever2019s life offers remarkable insight into the twentieth century. Through his eyes, we relive the history of the past 50 years, witnesses to a tale of science and technology that is revealing in its scope and sweep.

The Congestion Mitigation and Air Quality Improvement Program: Assessing 10 Years of Experience – Special Report 264 - Transportation Research Board
TRB Special Report 264 - Congestion Mitigation and Air Quality Improvement Program: Assessing 10 Years of Experience recommends that Congress retain the sole federal surface transportation program that funds projects to reduce pollution and traffic congestion in areas that must comply with national air quality standards. The Congestion Mitigation and Air Quality Improvement (CMAQ) program was enacted as part of the surface transportation legislation authorized in 1991 to provide support for projects that would aid local efforts to meet the strict new federal deadlines imposed by the Clean Air Act Amendments (CAAA) of 1990. CMAQ was included in the reauthorization of surface transportation legislation in 1998 for another 6 years, and funding for this period was set at 8.1 billion. In the 1998 legislation, Congress also requested an evaluation of the effectiveness of the program and the cost-effectiveness of the projects funded by the program. CMAQ funds are focused primarily on the transportation control measures (TCMs) contained in the 1990 CAAA (with the exception of vehicle scrappage programs, which have not been permitted). TCMs are strategies whose primary purpose is to lessen the pollutants emitted by motor vehicles by decreasing highway travel (for example, bicycle, pedestrian, and some transit projects) and to encourage more efficient facility use (for example, projects focused on ridesharing and on traffic flow improvements, such as signal timing). In addition, CMAQ funds may be used for projects that reduce vehicle emissions directly, such as through vehicle inspection and maintenance programs and purchase of alternative-fueled transit vehicles. In the spirit of the legislation that originally authorized the program, decisions about project selection are made at the local level, usually by or through the local metropolitan planning organization. After reviewing the limited information available about these types of projects, the committee that evaluated the CMAQ program concluded that, when compared on the sole criterion of tons of emissions reduced per dollar spent, strategies aimed directly at emissions reductions2014such as emissions and fuel standards for new vehicles, well-structured inspection and maintenance programs, and vehicle scrappage programs2014are more cost-effective than the typical CMAQ TCMs, which tend to depend on changes in behavior. A few behaviorally based TCMs, however, such as pricing and regional ridesharing, compare favorably with vehicle- and fuel-based strategies. The committee recommended that the CMAQ program be continued, in part because it is a \